2012
DOI: 10.6064/2012/152365
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Aspects of Congenital and Idiopathic Scoliosis

Abstract: Congenital and idiopathic scoliosis represent disabling conditions of the spine. While congenital scoliosis (CS) is caused by morphogenic abnormalities in vertebral development, the cause(s) for idiopathic scoliosis is (are) likely to be varied, representing alterations in skeletal growth, neuromuscular imbalances, disturbances involving communication between the brain and spine, and others. Both conditions are characterized by phenotypic and genetic heterogeneities, which contribute to the difficulties in und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 117 publications
1
39
0
6
Order By: Relevance
“…3,39 To determine whether segmentation is disrupted in MZ ptk7 mutant embryos, we performed in situ hybridization of her7 and dlc (direct reporters of the Notch segmentation mechanism and nascent somite differentiation) 40 within the presomitic mesoderm of 18-20 somite-staged MZ ptk7 mutant embryos, looking for possible irregularities in gene expression. The PSM domain was broader and expanded relative to total body length in MZ ptk7 mutants, consistent with a role for Ptk7 in tailbud patterning and morphogenesis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3,39 To determine whether segmentation is disrupted in MZ ptk7 mutant embryos, we performed in situ hybridization of her7 and dlc (direct reporters of the Notch segmentation mechanism and nascent somite differentiation) 40 within the presomitic mesoderm of 18-20 somite-staged MZ ptk7 mutant embryos, looking for possible irregularities in gene expression. The PSM domain was broader and expanded relative to total body length in MZ ptk7 mutants, consistent with a role for Ptk7 in tailbud patterning and morphogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the MZ ptk7 mutant phenotype may be more reminiscent of non-syndromic mild or moderate cases of CS where individuals display relatively few CVMs at irregular locations along the length of the spine. 3 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The assessment of growth potential is essential because of different maturational statuses as well as the type of maturation and mandibular growth influence the diagnosis and prognosis of orthodontic treatment. Unraveling the genetic contributions for both conditions can help to provide improved genetic counseling, prevention, and treatment strategies for this phenotype [6]. Some studies reported that the benefits of early detection of IGF-1 gene might be as one of the principal mediators in promoting muscular and skeletal growth to optimize the timing of orthodontic treatment, indeed in orthopaedic treatment [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Mandibular asymmetry is the asymmetric growth of mandible that due to complicated postnatal growth abnormality of the mandibular condyle [3][4][5]. In understanding the genetic aspects of congenital and idiopathic scoliosis, Giampietro suggested that craniofacial asymmetry as one of the major clinical features of oculoauriculo-vertebral spectrum [6]. However, the abnormalities in the skeletal, nerve, endocrine systems, and connective tissue for both asymmetries in the bilateral joint of temporomandibular and spinal still unclear whether these are primary or secondary.…”
Section: Introductionmentioning
confidence: 99%